THE IMPACT OF THE EURO ADOPTION ON NASDAQ OM X BALTIC STOCK EXCHANGE. ANALYSIS BY STRUCTURAL BREAK TESTS - Jakučionytė, Eglė (Ekonomika, 2011)
Although the euro adoption in Estonia in 2011 and changing the trading and clearing currency at the NASDAQ OMX Vilnius for euro on 22 November 2010 were foreseen as a possibility to attract more foreign investors, last year the Baltic stock exchange underwent some extreme fluctuations, both positive and negative. In this paper, shown are statistically significant euro adoption-caused trend breaks underlying the data set of NASDAQ OMX stock exchanges in Tallinn and Vilnius. Also, the possible factors that may have been driving them are discussed. The assessment is carried out using three different structural break tests.